2022
DOI: 10.1155/2022/1735204
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of the Influence of Caffeinated Coffee Consumption on the Concentrations of Serum Prolactin and Selected Parameters of the Oxidative-Antioxidant Balance in Young Adults: A Preliminary Report

Abstract: We verified whether caffeinated coffee consumption influenced the concentrations of prolactin (PRL) and oxidative stress parameters: total antioxidant status (TAS), ferric reducing antioxidant power (FRAP), total oxidant status (TOS), oxidative stress index (OSI), advanced oxidation protein products (AOPP), uric acid (UA), total bilirubin (T-Bil), albumin (ALB), iron (Fe), calcium (Ca), magnesium (Mg), and inflammatory marker C-reactive protein (CRP)—in blood sera obtained at 15, 60, and 120 minutes after caff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…Previous study showed that a moderate dose of PRL promotes the antioxidant capacity of adult RPE 19 human cells by reducing glutathione ( Melendez Garcia et al, 2016 ), suggesting PRL could exert an antioxidant action. However, several studies have discovered that HPC leads to oxidative stress in mammals ( Farmer, Lapointe & Cormier, 2017 ), with an increase in ROS generation and alterations to antioxidant system components ( Rodak et al, 2022 ), which is consistent with the results of the present study. In our study, the level of ROS in the four ng/mL group was decreased, the content of MDA depressed, and the levels of SOD and T-AOC were increased compared to other groups, but the results of the 500 ng/ml group showed the opposite trend.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous study showed that a moderate dose of PRL promotes the antioxidant capacity of adult RPE 19 human cells by reducing glutathione ( Melendez Garcia et al, 2016 ), suggesting PRL could exert an antioxidant action. However, several studies have discovered that HPC leads to oxidative stress in mammals ( Farmer, Lapointe & Cormier, 2017 ), with an increase in ROS generation and alterations to antioxidant system components ( Rodak et al, 2022 ), which is consistent with the results of the present study. In our study, the level of ROS in the four ng/mL group was decreased, the content of MDA depressed, and the levels of SOD and T-AOC were increased compared to other groups, but the results of the 500 ng/ml group showed the opposite trend.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the low concentration (four ng/mL) of PRL promoted cell proliferation and inhibited cytotoxicity, while HPC showed the opposite effect in ovine ovarian GCs, which was consistent with the previous study. Additionally, PRL has also been reported to play an important role in oxidative-antioxidant balance ( Farmer, Lapointe & Cormier, 2017 ; Rodak et al, 2022 ). Previous study showed that a moderate dose of PRL promotes the antioxidant capacity of adult RPE 19 human cells by reducing glutathione ( Melendez Garcia et al, 2016 ), suggesting PRL could exert an antioxidant action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Siener et al conducted experiments on ten men between the ages of 20 and 31 and found that the consumption of 1.5 L/day of black tea resulted in a signi cant increase in urinary citrate excretion by 21% over the 24-h urine collection period, which is an important inhibitor of calcium stone formation (30). Whereas in the study by Rodak et al, the substances contained in caffeinated coffee decrease the level of prolactin, which is an important hormone for women with more than 300 described functions, including regulation of reproductive function, the immune system, osmotic balance, and angiogenesis (31). This also suggests us that we should do more research on the caffeine contained in tea.…”
Section: Discussionmentioning
confidence: 98%